Modelling of wind energy‐based microgrid system implementing MMC. (21st January 2016) - Mishra, Sambeet; Palu, Ivo; Madichetty, Sreedhar; Suresh Kumar, L.V.
Summary: Nowadays, renewable energy systems have come up with more potential in power generation so as to meet the power demand. Among all the renewable systems, the wind energy generating system is believed to be at the peak. However, the wind energy‐based microgrid system is associated with many problems such as fluctuations in output voltage due to the fluctuated wind speeds and harmonics generations in the system. To address these issues, this article proposes a new method in order to achieve harmonic mitigation across its output by maintaining constant voltage. Nevertheless, particular attention has been given to the form and function of modular multilevel converter with multi‐winding transformer connected to the grid. Modular multilevel converter has been implemented with an advanced voltage controller tuned to control the voltage at its output. Also, a new system topology has been introduced with two wind turbines that are interconnected to multi‐winding transformer through asynchronous generators. The proposed system has been implemented with constant and variable wind speeds, and their respective results have also been analysed. The proposed scheme shows its effectiveness by theoretical calculations, verified by simulation and experimental results. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A new application for wind energy systems with Modular Multi‐level Converter has been presented with current and voltage controllers. Active and reactive power compensation details have been highlighted for variable wind speed. Capacitor ripple compensation has been observed with proposed controller and achieved 1.3% total harmonic distortion. A mathematical model for multi‐winding transformer is also developed in conjunction with Modular Multi‐level Converter. Simulation and experimental results have been presented.